Rephrasing Character Action for the Feiticeiro/a: External Coherence Through Transactional Relations - Theo, LJ (Constructing Transgressive Sexuality in Screenwriting: The Feiticeiro/a as Character, 2017)
If character actions are not to be seen in deterministic ways, then an alternative framing should be considered on which writers might base constructs of complexity of action. This is possible if action itself is seen as an expression of relationality rather than as activity-as-substance. Looking at people in this way enables the behaviour of Feiticeiro/a characters to be seen as activities that are more than the actions of combinations of sexed bodies in physical spaces. This chapter explores a construct for action on this basis as it becomes possible by acknowledging in a construct of ‘doing’ the phenomenological notions of ‘being’ as a Feiticeiro/a form constituted by a hybrid of ‘object-discourse-nature-society’ characterised by networks of confluence. The chapter explores the notion of the Feiticeiro/a character in terms of an internal coherency, taking account of interactions and activities (as exhibited through their material form), ‘naturalness’, linearity of course of action and embodied notions of meaning-creation.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Recherche-création; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé